Welfare Impact of Carbon Dioxide Euthanasia on Laboratory Mice and Rats: A Systematic Review - Turner, Patricia V.; Hickman, Debra L.; van Luijk, Judith; Ritskes-Hoitinga, Merel; Sargeant, Jan M.; Kurosawa, T. Miki; Agui, Takashi; Baumans, Vera; Choi, Woo Sung; Choi, Yang-Kyu; Flecknell, Paul A.; Lee, Byeong H.; et al. (Frontiers in Veterinary Science, 2020)
Background: There has been increased concern about the suitability of CO2 as a method for euthanasia of laboratory mice and rats, including the potential discomfort, pain or distress that animals may experience prior to loss of consciousness; time to loss of consciousness; best methods for use of CO2; and the availability of better alternatives. These discussions have been useful in providing new information, but have resulted in significant confusion regarding the acceptability of CO2 for rodent euthanasia. In some cases, researchers and veterinarians have become uncertain as to which techniques to recommend or use for euthanasia of laboratory mice and rats. Methods: The International Association of Colleges of Laboratory Animal Medicine (IACLAM) convened a taskforce to examine the evidence for adverse welfare indicators in laboratory rats and mice undergoing CO2 euthanasia using a SYRCLE-registered systematic review protocol. Of 3772 papers identified through a database search (PubMed, Web of Science, CAB Direct, Agricola, and grey literature) from 1900 to 2017, 37 studies were identified for detailed review (some including more than one species or age group), including 15 in adult mice, 21 in adult rats, and 5 in neonates of both species. Experiments or reports were excluded if they only assessed parameters other than those directly affecting animal welfare during CO2 induction and/or euthanasia. Results: Study design and outcome measures were highly variable and there was an unclear to high risk of bias in many of the published studies. Changes in the outcome measures evaluated were inconsistent or poorly differentiated. It is likely that repeated exposures to carbon dioxide inhalation are aversive to adult rats and mice, based on avoidance behavior studies; however, this effect is largely indistinguishable from aversion induced by repeated exposures to other inhalant anesthetic gasses. Conclusion: There is insufficient evidence to permit an unbiased assessment of the effect of CO2 inhalation during euthanasia on welfare indicators in laboratory mice and rats. Additional well-designed, unbiased, and adequately powered studies are needed to accurately assess the welfare of laboratory mice and rats undergoing euthanasia via CO2 gas.